2010
DOI: 10.1094/mpmi-04-10-0097
|View full text |Cite
|
Sign up to set email alerts
|

A Host-Factor Interaction and Localization Map for a Plant-Adapted Rhabdovirus Implicates Cytoplasm-Tethered Transcription Activators in Cell-to-Cell Movement

Abstract: To identify host factors that play critical roles in processes, including cell-to-cell movement of plant-adapted rhabdoviruses, we constructed and validated a high-resolution Nicotiana benthamiana yeast two-hybrid library. The library was screened with the putative movement protein (sc4), nucleocapsid (N), and matrix (M) proteins of Sonchus yellow net virus (SYNV). This resulted in identification of 31 potential host factors. Steady-state localization studies using autofluorescent protein fusions to full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 66 publications
2
49
1
Order By: Relevance
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 87%
“…The self-interaction of P protein was also reported for SYNV (Min et al, 2010) and LNYV , however was not observed for PYDV (Bandyopadhyay et al, 2010). The subnuclear localization of the ADV P:P complex (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations